2011
DOI: 10.1016/j.devcel.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β Cell Identity Is Maintained by DNA Methylation-Mediated Repression of Arx

Abstract: Summary Adult pancreatic beta cells can replicate during growth and after injury to maintain glucose homeostasis. Here we report that beta cells deficient in Dnmt1, an enzyme that propagates DNA methylation patterns during cell division, were converted to alpha cells. We identified the lineage determination gene aristaless related homeobox (Arx), as methylated and repressed in beta cells, and hypo-methylated and expressed in alpha cells and Dnmt1-deficient beta cells. We show that the methylated region of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
238
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(255 citation statements)
references
References 39 publications
9
238
4
Order By: Relevance
“…Cell plasticity has been intensively investigated in adult pancreatic endocrine cells. Lineage tracing analyses of adult pancreatic cells for various in vivo conditions clearly demonstrate that conversion between different pancreatic cell types occurs in adults through changes in the expression of transcription factors that are critical for endocrine cell differentiation [3][4][5][6][7][8]. These findings are supported by studies reporting that the forced expression of transcription factors convert cell types [9][10][11].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Cell plasticity has been intensively investigated in adult pancreatic endocrine cells. Lineage tracing analyses of adult pancreatic cells for various in vivo conditions clearly demonstrate that conversion between different pancreatic cell types occurs in adults through changes in the expression of transcription factors that are critical for endocrine cell differentiation [3][4][5][6][7][8]. These findings are supported by studies reporting that the forced expression of transcription factors convert cell types [9][10][11].…”
Section: Introductionsupporting
confidence: 75%
“…The expression of DNA methyltransferases was analysed because the loss of DNA methyltransferase (DNMT) 1 or DNMT3a results in a conversion from beta cell to alpha cell [4,5]. Dnmt1 and Dnmt3a expression was decreased in the Mafa KO islets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Vice versa, Arista-less-related homeobox (ARX), a master gene for a-cells, is normally methylated and repressed in pancreatic b-cells by DNMT1 with concomitant preservation of b-cell identity. 21 Therefore, it has been proposed that b-cell identity depends on the epigenetically controlled antagonistic activities of PAX4 and ARX, but the fine tuning mechanisms are still unclear. 21 Beside passive demethylation (inhibition of DNMTs), active demethylating mechanisms involving TET enzymes can also be involved in the correct development of pancreatic islets.…”
Section: B-cell Development and Functionmentioning
confidence: 99%
“…21 Therefore, it has been proposed that b-cell identity depends on the epigenetically controlled antagonistic activities of PAX4 and ARX, but the fine tuning mechanisms are still unclear. 21 Beside passive demethylation (inhibition of DNMTs), active demethylating mechanisms involving TET enzymes can also be involved in the correct development of pancreatic islets. 10 A relatively recent study on heterozygous miR-26a transgenic mice showed reduced expression of TET2 during islet postnatal differentiation and increased postnatal islet cell number.…”
Section: B-cell Development and Functionmentioning
confidence: 99%
“…First, epigenetic regulators can decide the reprogramming process by themselves. For example, pancreatic beta cells can be reprogrammed into alpha cells by DNA methyltransferase Dnmt1 deficiency (Dhawan et al, 2011). Second, epigenetic regulators can interact with exogenous factors to re-activate or suppress related gene expression.…”
Section: Epigenetic Regulatorsmentioning
confidence: 99%